Influence of Leadership Competencies on Extension Workers’ Performance in Yemen - Khalil, Ali Hassan; Ismail, Maimunah; Suandi, Turiman; Silong, Abu Daud (2008)
This article examines the relationship between leadership competencies variables of extension workers, namely, human development learning, leadership development, extension and communication methods, program planning, program implementation and program evaluation with performance of agricultural extension workers in Yemen. Data were collected from 290 respondents who were selected based on a stratified sampling technique. Regression analysis was utilized to examine the contribution of the variables to performance of agriculture extension workers. The findings show that three variables were significantly contributed to the level of extension worker performance. The variables are competencies in extension program implementation, extension evaluation and extension program planning. These predictor variables explain 42.2 % of the variance in the job performance of extension workers. The study suggests that relevant ministry such as the ministry of agriculture should take into account the level of leadership competencies and how to improve the competencies of extension workers in order to upgrade their performance in developing rural communities through extension services.